The diarrhetic shellfish-poisoning toxin, okadaic acid, provokes gastropathy, dysbiosis and susceptibility to bacterial infection in a non-rodent bioassay, Galleria mellonella - Helena Emery (Archives of Toxicology, 2021)
Diarrhetic shellfish-poisoning (DSP) toxins such as okadaic acid and dinophysistoxins harm the human gastrointestinal tract, and therefore, their levels are regulated to an upper limit of 160 μg per kg tissue to protect consumers. Rodents are used routinely for risk assessment and studies concerning mechanisms of toxicity, but there is a general move toward reducing and replacing vertebrates for these bioassays. We have adopted insect larvae of the wax moth Galleria mellonella as a surrogate toxicology model. We treated larvae with environmentally relevant doses of okadaic acid (80–400 μg/kg) via intrahaemocoelic injection or gavage to determine marine toxin-related health decline: (1) whether pre-exposure to a sub-lethal dose of toxin (80 μg/kg) enhances susceptibility to bacterial infection, or (2) alters tissue pathology and bacterial community (microbiome) composition of the midgut. A sub-lethal dose of okadaic acid (80 μg/kg) followed 24 h later by bacterial inoculation (2 × 105 Escherichia coli) reduced larval survival levels to 47%, when compared to toxin (90%) or microbial challenge (73%) alone. Histological analysis of the midgut depicted varying levels of tissue disruption, including nuclear aberrations associated with cell death (karyorrhexis, pyknosis), loss of organ architecture, and gross epithelial displacement into the lumen. Moreover, okadaic acid presence in the midgut coincided with a shift in the resident bacterial population over time in that substantial reductions in diversity (Shannon) and richness (Chao-1) indices were observed at 240 μg toxin per kg. Okadaic acid-induced deterioration of the insect alimentary canal resembles those changes reported for rodent bioassays.